Konversi Sepeda Motor Yamaha Mio Sporty Menjadi Sepeda Motor Listrik dengan Metode Sambung Langsung - Aken Derisman; Muhammad Ridha Fauzi; Denur, Denur; Japri, Japri; Jusnita, Jusnita; Zikri, Zikri (Fakultas Teknik UMRI, 2024)
The shift from Petrol powered vehicles to electric vehicles, especially motorcycles, is ongoing. Although this has many benefits, such as reducing air pollution, a problem arises in the form of unused Old Year Petrol-powered Motorcycles, which can become environmental waste. In facing this problem, the idea arose to convert unused petrol-powered motorcycles into electric motorcycles. The main goal is that unused Petrol-powered motorcycles can be reused by replacing their engines with electric engines. The results of the vehicle speed test, the maximum speed obtained by the Electric vehicle is 40 km / h, while for the Torque and Power of the Electric motorcycle were tested using a dynotest tool with the highest Torque results obtained at 1867 rpm of 7.17 Nm and the lowest torque at 2500 rpm with a result of 0.54 Nm. For the highest Power obtained at 1903 rpm with a result of 1.9 HP and the lowest power obtained at 2500 rpm with a result of 0.2 HP.